Structural Characteristics of Reinforced Palm Kernel Shell Concrete Deep Beams - Mark Adom-Asamoah; Jack Banahene Osei; Kwadwo Adinkra-Appiah (Salehan Institute of Higher Education, 2018)
This paper evaluates the structural characteristics of deep beams made from reinforced palm kernel shell concrete (PKSC) and normal weight concrete (NWC). Twelve PKSC and NWC deep beam samples, with and without shear reinforcement were tested under three-point loading and their structural behavior studied. The ultimate shear strength of PKSC beams increased with a decrease in the shear span-to- depth ratio. Post diagonal cracking shear resistance is greater in PKSC deep beams than beams of normal weight concrete. The shear capacity of the PKSC and NWC deep beams were assessed to be un-conservative using ACI 318-99, ACI 318-05, Eurocode (EC) 2 and a kinematic model, when compared with the experimental results. Nonetheless, this necessitated the development of a calibration procedure to correct the bias inherent in these models. Calibrated shear strength models revealed the compressive strength and the ratio of the shear span-to-total depth as significant influential parameters for correcting the inherent bias in the original deterministic shear strength models. The calibrated functional model of ACI-318-99 may produce conservative predictions, given this limited number of test specimens. Therefore future studies should investigate the reliability of the calibrated models, and quantifying the uncertainties in the estimated coefficients of parameters, using a much larger representative dataset.